Sustainable Livelihood Index for Sharia-Based Micro, Small, and Medium Enterprises: A Feyerabendian Approach - Sukriyah; Khomsiyah (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Micro, small, and medium enterprises that operate according to Islamic principles form a vital part of Indonesia’s economy, yet existing sustainability measurement tools rarely reflect their unique ethical and spiritual characteristics. This study aims to develop a conceptual model of the Sustainable Livelihood Index specifically designed for these Sharia-based enterprises. The research adopts a qualitative conceptual approach that combines philosophical analysis and extensive literature review, guided by Paul Feyerabend’s principles of methodological pluralism and theoretical proliferation. Core Islamic values such as distributive justice, social responsibility, environmental stewardship, trustworthiness, and sincerity are systematically integrated into the five traditional dimensions of human, physical, financial, social, and environmental capital. The resulting model presents a hierarchical framework supported by concrete sample indicators that are both practical and faithful to Islamic teachings. This new index offers a flexible, context-sensitive tool that captures economic, ethical, social, and spiritual performance simultaneously. The model has direct implications for entrepreneurs, Islamic financial institutions, and policymakers seeking to strengthen sustainable and resilient Sharia-compliant economic development. It also lays a solid foundation for future empirical testing and wider application across the Muslim business community.